PSIKOEDUKASI PENINGKATAN SELF COMPASSION DALAM PEIRLAKU BERPACARAN PADA REMAJA - Puspitasari, Elya Ika; Indriani, Vanny Noviana; Aini, Yulia Nur; Abidah, Isna Maulida; Maryam, Effy Wardati (Journal of Social Comunity Services, 2024)
Psychoeducation is an educational method given to a group of teenagers with the aim of providing knowledge about the importance of self-compassion to reduce dating behavior in teenagers, especially junior high school students. Self-compassion appears to be a more positive variable in efforts to develop teenagers' self-concept. Through self-compassion, teenagers understand that they need to be kind to themselves (self-kindness) and think that the situation they are currently experiencing can also be experienced by other people (common humanity) and get full recognition when carrying out an action (mindfulness). The research used a quantitative approach with a sample of 108 students. Quantitative data was obtained by giving a pre-test and post-test, then data processing was carried out using the T Test. The results showed that there were significant changes between the dating behavior of students before and after being given self-compassion understanding psychoeducation where self-compassion psychoeducation had an effect on reducing dating behavior in students